NILAI PENDIDIKAN KARAKTER PADA KUMPULAN CERITA RAKYAT KOTA SINGKAWANG 2019 - Kartika, Indah; Sunarsih, Eti; Safrihady, Safrihady (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the Value of Character Education in the Collection of Folk Tales of Singkawang City 2019. The method used is a descriptive method. The form of this research is qualitative. Data sources are in the form of quotations and data in the form of character education values. The data collection technique is a documentary study technique. The data analysis technique is carried out by collecting quotations, analyzing, comparing, and combining them to form systematic and complete study results, based on data analysis and discussion it can be concluded that the value of character education based on heart processing has 57 data, based on thinking processing there are 19 data, based on sports there are 10 data, based on feeling and intention processing there are 23 data. This research can be implemented in class IX applied as Indonesian language teaching materials for Film/Drama material for the Independent Curriculum with Learning Achievements (CP) for writing and listening elements.